PENILAIAN KINERJA MANAJER KEPERAWATAN BERDASARKAN BALANCED SCORE CARD DAN FUNGSI MANAJEMEN: LITERATUR REVIEW - Yulistina, Putu Desi; Suyasa, I Gede Putu Darma; Rismawan, I Made; Sandra, Putu Yudara (Poltekkes Kemenkes Bandung, 2024)
One reason for the need for standardized assessment of nurse managers is to ensure their performance evaluations are consistent and objective. This research aimed to be used as a reference in conducting performance assessments at the nurse manager level. This research uses the Literature review method using the PRISMA flow diagram. An article search using 3 journal databases including Scopus, Google Scholar, and Pubmed, obtained 20 final articles published between 2018 and 2023. The results of the research show that the performance assessment of nurse managers includes 4 BSC perspectives and is oriented towards management functions and the five core competency domains of nursing. The performance assessment of nurse managers includes competency knowledge, skills and attitudes which are then linked to the implementation of management roles and functions (planning, organizing, driving and controlling) both from the dimensions of human resources, environment and business or cost control. The performance assessment of nurse managers can be adjusted to the level or career path of nurse managers from level I to level V which is divided into top, middle and low managers. Assessment instruments related to assessing the performance of nurse managers have not been standardized and are still diverse. Several regulations in Indonesia do not yet include competency and assessment standards for nurse managers. The BSC can be used as basis for preparing nurse manager performance assessment instrument which includes 4 perspectives, oriented towards management functions, and 5 core nursing competency domains.